Peran Perempuan dalam Kesetaraan Gender di Partai Politik (Studi di Partai Keadilan Sejahtera Kota Medan) - Adinda Tasya Azzahra Hasibuan; Elly Warnisyah Harahap (Dinasti Review, 2024)
The study aims to explore the role of women in the efforts to gender equality in the City of Medan's Party of Welfare Justice (PKS). The research method used is a political approach with qualitative analysis using data collection techniques of in-depth interviews of a number of women members of the PKS of the City of Medan. The results of the study reveal that women in the CCP have a significant role in the fight for gender equality, both in the political and social sphere. In addition, the findings of the study also identify the challenges and obstacles faced by women in their efforts to gender equality in the CMC of Medan. The research highlights the importance of a deeper understanding of the role of women in political and gender equality contexts, as well as providing valuable insights for more inclusive and sustainable policy development in the future.